Magnetoelectric effect and the upper critical field in superconductors without inversion center: Сверхпроводимость и сверхтекучесть - Mineev, V.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Solving the Ginzburg–Landau equation we demonstrate that the paramagnetic limiting of superconducting state in the superconductors without space inversion symmetry is significantly weakened. It is caused by so called magnetoelectric mechanism proving to be effective or not depending of the magnetic field direction and the crystal symmetry.